MECHANISMS FOR ENSURING DEMOCRATIC CIVILIAN CONTROL IN THE SPHERE OF ADMINISTRATIVE RESPONSIBILITY OF MILITARY PERSONNEL - Klymenko, Nataliia (Public Management and Policy, 2026)
The article provides a comprehensive theoretical justification and offers practical recommendations for developing a system of democratic civilian control over the administrative responsibility of military personnel in Ukraine. The relevance of the research is determined by the need to transform the security and defense sector in accordance with NATO standards and the requirements of the martial law legal regime. The author states that the current system of administrative responsibility is characterized by “legal dualism”, caused by contradictions between the Code of Ukraine on Administrative Offenses and the Disciplinary Statute, which creates a basis for excessive command discretion and violation of the rights of military personnel as “citizens in uniform”. The work proposes and details six strategic control mechanisms. First, the institutionalization of the Military Ombudsman based on the German model as a body of parliamentary oversight is substantiated. Second, the strengthening of judicial supervision through the specialization of civilian judges is proposed, which will ensure professional consideration of cases while maintaining independence from the military hierarchy. The third mechanism is identified as the transformation of the Military Law Enforcement Service into a full-fledged Military Police with procedural independence, which will allow for the separation of investigative and decision-making functions. The fourth aspect highlights the digitalization of records through the Unified Electronic Register, ensuring the transparency of statistics for civil society. The fifth element is identified as the development of military advocacy and free legal aid based on the Canadian model. The final mechanism is the codification of legislation through the adoption of the Code of Military Justice of Ukraine. It is proven that the implementation of these mechanisms will ensure the transition from a punitive to a service-oriented model, where the strengthening of discipline is based on the principles of justice and the rule of law. The study’s conclusions can be used in reforming the regulatory and legal framework of Ukraine and implementing Euro-Atlantic standards into the daily activities of the Armed Forces.